Time doesn’t heal all: PTSD symptoms exacerbate the relationship between age and pain intensity - O’Connor, Victoria; Rowland, Jared A.; Naylor, Jennifer C.; Magnante, Anna T.; Craig, Katherine M.; Miskey, Holly M.; , VA Mid-Atlantic MIRECC Workgroup; Beckham, Jean C.; Calhoun, Patrick S.; Dedert, Eric; Elbogen, Eric B.; Fairbank, John A.; et al. (Frontiers in Psychiatry, 2023)
Objective: Posttraumatic stress disorder (PTSD) symptoms and pain interfere with daily functioning and quality of life for many combat Veterans. As individuals age, pain symptoms tend to increase whereas PTSD symptoms tend to decrease. PTSD symptoms exacerbate pain, but the nature of this relationship across the aging process is unclear. The purpose of this study was to determine how PTSD symptoms affect the association between age and pain intensity.Methods: Participants in this cross-sectional study included 450 Veterans (80% male) who served after September 11, 2001. PTSD and pain intensity ratings were assessed by the PTSD Checklist for DSM-5 (PCL-5) and the Brief Pain Inventory (BPI), respectively. Hierarchical multiple linear regression evaluated main and interaction effects between age, PTSD symptoms, and pain intensity.Results: Age (B = .04, p < .001) and PTSD symptoms (B = .05, p < .001) were positively associated with pain intensity. Age and PTSD symptoms were inversely correlated (r = -.16, p < .001). PTSD symptoms exacerbated the relationship between age and pain intensity (ΔR 2 = .01, p = .036). Specifically, when greater PTSD symptoms were reported at older ages, pain intensity was significantly higher.Results of these analyses suggests that age is important when considering the effects of PTSD symptoms on pain intensity ratings. Specifically, pain intensity ratings are higher in older Veterans with PTSD symptoms. These findings underscore the importance for clinical providers to evaluate trauma history and PTSD symptoms in older Veterans reporting pain symptoms.This study contributes additional understanding of the relationship between pain and PTSD across the lifespan. When greater PTSD symptoms are present at older ages, Veterans report greater pain intensity. Providers should assess for trauma and PTSD symptoms among older Veterans reporting pain as a potential additional avenue of treatment.